Trisomy 21 in forensic autopsies: Review of a 20-year period. (April 2019) - Holz, F.; Plenzig, S.; Held, H.; Verhoff, M.A.; Birngruber, C.G.
Highlights: Forensic autopsy cases of decedents with trisomy 21 are very rare (0.14% of all autopsy cases during a 20-year-period). In 69.6% of the cases, the manner of death was classified as natural with fatal infections being the main cause of death. The study did not reveal any homicidal or suicidal deaths. When assessing allegations of medical malpractice, the higher susceptibility, and the higher risk for fatal courses of presumed uncomplicated e.g. respiratory infections in patients with trisomy 21 must be kept in mind. Abstract: Background: Trisomy 21 is the most common human chromosomal abnormality. Its manifestation includes intellectual impairment and more or less typical anatomical malformations and functional deficiencies that can cause sudden or unexpected deaths. Typical medicolegal questions at autopsy are related to medical malpractice, improper care, neglect, or abuse, and, depending on the cause of death, whether the death might have been avoidable. The aim of this study was to examine whether the causes of death in individuals with trisomy 21 were linked to the known health risks for this condition and to consider how these deaths might have been prevented. Material and methods: A retrospective study was performed at the Institutes for Legal Medicine in Giessen and Frankfurt am Main, Hesse, Germany. All records for forensic autopsy cases within a 20-year period from 1998 to 2017 were reviewed for the diagnosis trisomy 21", respectively, "Down's syndrome". Results: Twenty-three cases complied with the inclusion criteria trisomy 21 and autopsy. The age of the deceased ranged from 23 days to 61 years. Infectious diseases, mainly respiratory, were the leading cause of death, followed by accidental deaths. Conclusion: The medicolegal relevance of the known health risks in Down's syndrome could be illustrated by the autopsy findings and the results of the additional examinations. The known high susceptibility to infections, with an increased risk of a rapid course and lethal outcome, in individuals with Down's syndrome could be confirmed in our study. A sound knowledge of the risks and abnormalities associated with trisomy 21 are helpful in medicolegal assessments, particularly, in relation to medical malpractice charges.